1999
DOI: 10.1159/000012017
|View full text |Cite
|
Sign up to set email alerts
|

Dose Intensification of Platinum Compounds with Glutathione Protection as Induction Chemotherapy for Advanced Ovarian Carcinoma

Abstract: Based on previous clinical experience indicating the tolerability and efficacy of high-dose cisplatin with glutathione protection in the treatment of advanced ovarian cancer, this study was undertaken to explore the efficacy and feasibility of an alternative high-dose, platinum-based approach including a combination of high-dose cisplatin plus carboplatin as induction chemotherapy of advanced ovarian carcinoma and intervention surgery. Fifty consecutive eligible patients with untreated stage III or IV epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…These patients present with tinnitus and/ or hearing loss in high frequencies; but cisplatin can also affect the speech frequencies (Nagy et al, 1999). Although the dose of cisplatin given is an important factor in achieving optimal antineoplastic effects (Bohm et al, 1999), high doses can cause serious side effects, for example, peripheral neuropathies, renal insufficiency and sensorineural hearing loss. Hearing impairment is dose related, cumulative, bilateral and usually permanent.…”
Section: Introductionmentioning
confidence: 99%
“…These patients present with tinnitus and/ or hearing loss in high frequencies; but cisplatin can also affect the speech frequencies (Nagy et al, 1999). Although the dose of cisplatin given is an important factor in achieving optimal antineoplastic effects (Bohm et al, 1999), high doses can cause serious side effects, for example, peripheral neuropathies, renal insufficiency and sensorineural hearing loss. Hearing impairment is dose related, cumulative, bilateral and usually permanent.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that maintenance of high reduced to oxidized glutathione ratio is an important intracellular event for proper renal functions. Other studies have also shown the importance of intracellular glutathione in protecting against toxicity induced by platinum containing anticancer agents (Fontanelli et al 1992;Hamers et al 1993;Babu et al 1995;Bohm et al 1999;Hu et al 1999). Moreover, carboplatin at higher doses significantly increased renal glutathione-Stransferase activity indicating that the renal system is compensated in response to high doses of carboplatin to conjugate it with glutathione and thereby detoxified and excreted out through the kidney.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies had shown that carboplatin is toxic at a dose of (100-200 mg/kg, intraperitoneally) to rats (Kimura et al 1989;Nonclercq et al 1989;Haragsim & Zima, 1992;Blommaert et al 1996;Husain et al 2001). These doses are equivalent to the clinical therapeutic doses of carboplatin in cancer patients (Bishop 1992;Bohm et al 1999;Wandt et al 1999;Maldoon et al 2000). However, administration of high and/or cumulative doses of carboplatin produced renal toxicity in humans (Agraharkar et al 1998;English et al 1999) and experimental animals (Ueda et al 1991;Martinez et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 There have been several other phase 2 trials showing the same positive result. [62][63][64] Although the latter were nonrandomized phase 2 trials, there have also been randomized trials of the same concept. In one study, 151 patients received cisplatin for ovarian cancer.…”
Section: Cisplatin and The Problem Of Ototoxicitymentioning
confidence: 99%